2000
DOI: 10.1046/j.1460-9568.2000.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide and NO synthase inhibition on nonquantal acetylcholine release in the rat diaphragm

Abstract: After anticholinesterase treatment, the postsynaptic muscle membrane is depolarized by about 5 mV due to nonquantal release of acetylcholine (ACh) from the motor nerve terminal. This can be demonstrated by the hyperpolarization produced by the addition of curare (H-effect). The magnitude of the H-effect was decreased significantly to 3 mV when the nitric oxide (NO) donors, sodium nitroprusside (SNP) and S-nitroso-N-acetylpenicillamine (SNAP) were applied to the muscle, or when NO production was elevated by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 62 publications
(132 reference statements)
10
44
0
Order By: Relevance
“…Thus it was used as further evidence that the observed responses were NO mediated. Because hemoglobin does not enter cells and it scavenges NO extracellularly (37), it may scavenge NO generated intracellularly by creating a diffusion gradient of NO out of the cell "sink" (27).…”
Section: L-nmma Hemoglobin and Sp-nomentioning
confidence: 99%
“…Thus it was used as further evidence that the observed responses were NO mediated. Because hemoglobin does not enter cells and it scavenges NO extracellularly (37), it may scavenge NO generated intracellularly by creating a diffusion gradient of NO out of the cell "sink" (27).…”
Section: L-nmma Hemoglobin and Sp-nomentioning
confidence: 99%
“…The mechanism of neuropeptide action is realized through its extracellular hydrolysis by the GCP II with the formation of glutamate molecules, which, as was shown earlier [89], activate glutamate postsynaptic NMDA receptors and thereby trigger the NO-mediated mechanism of reducing the intensity of the non-quantal ACh release [104].…”
Section: Peptidergic Signalingmentioning
confidence: 84%
“…The inhibitory action of nitric oxide on spontaneous and induced synaptic currents was shown also in the developing neuromuscular contacts Xenopus laevis [154]. In contrast with endplate of amphibian, NO has no effect on spontaneous and evoked forms of quantal ACh release, but significantly reduces the intensity of non-quantal release of ACh in mammalian NMJ [104]. However, as was shown later, NO can modulate the quantal release in mammals, enhancing transmitter release from motor nerve via a cGMP pathway, but it occurs only when adenosine A1 receptors were blocked [155].…”
Section: Physiological Effects Of No In Nmjmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, skeletal muscle nNOS was reported to play a role in the regulation of a number of cellular processes such as contractile activity, glucose uptake, and blood flow distribution, but the importance of sarcolemmal targeting of nNOS for these regulatory functions is largely unknown 22 More importantly, authors found that diaphragmatic NOS activity during postnatal development was strongly controlled at multiple levels, including gene transcription. An endogenous inhibitor, the newly discovered PIN (protein inhibitor of nNOS) is known to be widely expressedin various skeletal muscles including the diaphragm, and to inhibit nNOS activity by preventing its dimerization.…”
Section: The Effect Of Nitric Oxide On the Rat Diaphragm At Differentmentioning
confidence: 99%